2018
DOI: 10.1111/1751-2980.12599
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Smad4 reduces hepatic inflammation and fibrogenesis during nonalcoholic steatohepatitis progression

Abstract: Smad4 deletion may inhibit lipogenesis, stimulate β-oxidation, improve lipid metabolism and liver function, alleviate inflammation and fibrosis, and reduce cell apoptosis in NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…So far, Takahashi et al reported a decrease in liver mass and liver fat content after administration of TGF-β2 in high-fat diet (HFD) treated mice [231]. Also of relevance, knockout of Smad4 stimulated β-oxidation of fatty acids and suppressed lipid-induced fibrosis and inflammation in mouse livers [233]. The distinct metabolic roles of TGF-β1 and 2 again highlight the non-redundant functions of these TGF-β isoforms.…”
Section: Tgf-β and Metabolic Fate Changes In Liver Fibrosismentioning
confidence: 99%
“…So far, Takahashi et al reported a decrease in liver mass and liver fat content after administration of TGF-β2 in high-fat diet (HFD) treated mice [231]. Also of relevance, knockout of Smad4 stimulated β-oxidation of fatty acids and suppressed lipid-induced fibrosis and inflammation in mouse livers [233]. The distinct metabolic roles of TGF-β1 and 2 again highlight the non-redundant functions of these TGF-β isoforms.…”
Section: Tgf-β and Metabolic Fate Changes In Liver Fibrosismentioning
confidence: 99%
“…IPA analysis of the mouse models also identified pathways that were not predicted to be affected among human NASH datasets. Among these, the activation of SMAD2, SMAD4, YAP1, NOTCH1, EP300, p63, and the inhibition of nuclear receptor corepressor (NCOR) has been previously linked to human NASH by independent studies ( Table 3 ) [ 42 , 166 , 173 , 209 , 210 , 211 , 212 ]. Therefore, most mouse models mimic the transcriptional signature of human NASH for these transcription factors.…”
Section: Prediction Of Transcriptional Regulators By Database Analmentioning
confidence: 99%
“…The findings of our literature survey confirmed the implication of the following: HSP90AB1 has been suggested as a possible biomarker in overweight and obese children with NAFLD [41]; HLA-B [42], CTNNB1 [43] and HSPA5 [44] are found to be abnormally expressed in NAFLD patients; CDKN1A polymorphism is associated with the development of human NAFLD [45]; TRAF1 has been also detected in NAFLD patients [46]; HSPB1 phosphorylation site has been differed between NAFLD cohorts [47]; SMAD4 was overexpresed in NASH patients [48]; SMAD2/3 phosphorylation and nuclear translocation documented in the liver of NASH patients[49]; RELA is well-known to cause inflammatory responses in NAFLD [50]; PIK3R3 has been proposed as an effective candidate target for the development of NAFLD [51]; GSK3B inhibition has been proposed as a possible therapeutic target to manipulate the NAFLD [52].…”
Section: Discussionmentioning
confidence: 99%